Between the bridges. - Bostrin, Klaus; Brookmann, Dieter; Giese, Jörg; Jast, Frank; Kreis, Elfi (Potsdam : Waschhaus e.V., 2000)
Armando ; Castelli, Luciano ; Commandeur, Jan ; Deleau, Roland ; Eisermann, Stefan ; Engel, Lilli ; Rheinsberg, Raffael ; Fetting, Rainer ; Gaudlitz, Frank ; Grimmling, Hans-Hendrik ; Henderikse, Jan ; Maslo, Olga ; Niblock, Phill ; Oppenheim, Dennis ; Ramolla, Susanne ; Shelley, Ward ; Sluik, Ron ; Kurpershoek, Reinier ; Timpson, Michael ; Yamanaka, Manabu
biog. + kleine tekst per kunstenaar
Duits
Between the bridges, Waschhaus e.V., Potsdam, 10. August 2000 bis 17. September 2000
boek